URGENSI FILANTROPI ISLAM UNTUK PEMBIAYAAN PENDIDIKAN ALTERNATIF BAGI ANAK-ANAK YANG TIDAK MAMPU - Kaulika, Syamela Massa (re-JIEM (Research Journal of Islamic Education Management), 2023)
The cost of education is the main factor that has a big influence on the implementation of learning activities. Indonesia has enough problems in the economy that have caused many children from families with low incomes to be forced to not attend school, due to the lack of education costs, even to meet their daily needs is still a burden. This is also a problem that must be addressed, so as not to create educational disparities and create educational equity. The settlement of these educational problems can be overcome through social activities with a pattern of income redistribution or commonly known as philanthropy. The purpose of this study is to explain the urgency of philanthropy for alternative financing in Islamic educational institutions. This research uses descriptive analytic literature study. The results of this study are (1) philanthropic practice has become an institutionalized tradition since the emergence of Islam. (2) philanthropy has an important role for alternative financing in Islamic educational institutions through zakat, alms, waqf and various obligations other than waqf. From the results of this research, the community can be more concerned and sensitive to social interests so that they can carry out philanthropic practices that are expected for education in Indonesia.